Different responses of primary normal human hepatocytes and human hepatoma cells toward cyanobacterial hepatotoxin microcystin-LR. (October 2015) - Ikehara, Tsuyoshi; Nakashima, Junichi; Nakashima, Shihoko; Yasumoto, Takeshi
Abstract: Microcystins (MCs) are potent hepatotoxins produced by cyanobacteria in aquatic environments. MC-LR, a representative MC, strongly inhibits protein phosphatases 1 and 2A, leading to cell collapse in animal hepatocytes due to hyperphosphorylation of the cytoskeleton and apoptosis due to stimulation of the relevant systems. However, the molecular mechanisms and the metabolic pathways responsible for MC-LR toxicity are poorly understood. In the present study, we compared the cytotoxic effects of MC-LR in two cell lines: normal human hepatocytes (h-Nheps) and human hepatoma cell line HepG2. We also discussed the suitability of cellular assays for evaluating the toxicity of MCs. To obtain further insight into the molecular mechanism, the uptake, excretion, and intracellular distribution of MC-LR were analyzed using an antibody and assay kit targeting the catalytic subunit of protein phosphatase 2A (the PP2A assay kit). The responses toward MC-LR were distinctly different between the two cell lines. In HepG2 cells, MC-LR did not induce morphological change, did not reveal cytotoxicity, and accumulated to a lesser extent despite a slightly elevated expression of the MC transporter protein. MC-LR also did not alter the MC-binding potency of subcellular proteins. All these results indicate that HepG2 cells are inappropriate for the evaluation of MC-LR toxicity. The PP2A assay kits were useful not only for assessing PP2A-inhibitory potency, but also for determining the concentration of MCs in biological systems.